2015
DOI: 10.1088/0960-1317/26/1/015009
|View full text |Cite
|
Sign up to set email alerts
|

Durable and mass producible polymer surface structures with different combinations of micro–micro hierarchy

Abstract: Extensive studies have been performed with the aim of fabricating hierarchical surface structures inspired by nature. However, synthetic hierarchical structures have to sacrifice mechanical resistance to functionality by introducing finer scaled structures. Therefore, surfaces are less durable. Surface micro–micro hierarchy has been proven to be effective in replacing micro–nano hierarchy in the sense of superhydrophobicity. However, less attention has been paid to the combined micro–micro hierarchies with sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…All three texture types are shown for PP (Figures 3 A-C) while only the protected micro-micro textured type is shown for the hard rubber (Figure 3 D) and the soft rubber (Figures 3 E, F). Various microtexture combinations on PP surfaces have been produced and investigated previously (Huovinen et al, 2014;Jiang et al, 2016;Mielonen et al, 2017). In the present study, these textures were successfully replicated on rubber surfaces as well.…”
Section: Accepted Manuscriptmentioning
confidence: 74%
“…All three texture types are shown for PP (Figures 3 A-C) while only the protected micro-micro textured type is shown for the hard rubber (Figure 3 D) and the soft rubber (Figures 3 E, F). Various microtexture combinations on PP surfaces have been produced and investigated previously (Huovinen et al, 2014;Jiang et al, 2016;Mielonen et al, 2017). In the present study, these textures were successfully replicated on rubber surfaces as well.…”
Section: Accepted Manuscriptmentioning
confidence: 74%
“…Normal loads up to 100 kg (corresponding to a surface pressure of 28 MPa) were pressed onto two different structures, i.e., dual-level pillars (DPLs) and pillars inside pits (PLiPTs). 93 Measuring the filtered roughness values revealed that the PLiPT structures showed no significant changes in the surface roughness values. For the DPL structures, the roughness in the 1−50 μm and 100−500 μm range were altered dramatically, while the roughness in the 50−100 μm range remained almost constant.…”
Section: Superhydrophobic Surfaces Produced Bymentioning
confidence: 98%
“…64,92 As such, the use of micromicro hierarchical structures was proposed as a solution for avoiding use of the more vulnerable micronano hierarchical structures that would be subjected to mechanical forces. 93 However, a comparative study that would evaluate micro-microstructured surfaces against micro-nanostructured surfaces composed of the same materials under specific mechanical loads is required to truly test this possibility.…”
Section: Superhydrophobic Surfaces Produced Bymentioning
confidence: 99%
“…First, small metallic inlays consisting of thin Al foils having dimensions of 15 mm × 20 mm × 250 µm were produced using a procedure previously developed at the Department of Chemistry of the University of Eastern Finland. Micro-pits having the dimensions (diameter and depth listed in Table 1) of the desired micro-pillared structures were produced in Al inlays using a hard-metal microneedle mounted on a computer-controlled micro-working robot (model RP-1AH, Mitsubishi Electric, Chiyoda, Japan), which enabled automated production of an array of such micro-pits over the whole Al foil area [29,30]. The size of the microneedle along with the robot parameters defined the final dimensions of the micro-pits.…”
Section: Geometry Dimensions Production and Characterization Of Surmentioning
confidence: 99%